General population awareness regarding iron deficiency anaemia and its relation with nutrition and dietary habits - Shehata, Shehata Farag; Alahmari, Faisal S.; Alahmari, Saad A.; Aljamaan, Abdulelah M.; Alamrah, Hussam M.; Alsharif, Naif M.; Almosa, Ahmad M.; Almosa, Hussain M. (International Journal Of Community Medicine And Public Health, 2020)
Background: Iron deficiency anaemia is considered as a significant public health problem in vulnerable groups especially adolescents. This necessitates the importance of awareness about the disease among general population. Also, public awareness regarding the significance of iron deficiency and its effect upon work performance, and the importance of providing iron during pregnancy and childhood is a mandatory health issue. Policy makers should focus their strategy right from adolescence beginning with raising awareness about iron deficiency anaemia. Methodology: A descriptive cross-sectional approach was applied targeting all population in Aseer region who aged 18 years or more from January 2020 to April 2020. Data were collected using online questionnaire through social media. Results: The survey respondents were 537 persons whose ages ranged from 18 to 89 years old with mean age of 32.1 12.2 years. Three hundred participants (55.9%) were males and 84.7% of them were at urban area. More than 70% of the respondents previously heard about Anaemia and 88.8% agreed on that anaemia is health problem. Iron as the nutrient deficient in anaemia was reported by 78.6% of the participants and 69.1% reported that in anaemia there is decreased haemoglobin level. Generally, about half of the participants had good awareness level regarding all aspects of IDA. Conclusions: the study revealed that the recorded awareness level regarding IDA was considerable with many areas of defect. The main areas of awareness defect included iron rich food and absorption inhibitors which indicates the urgent need for further effort to raise the population awareness and improving their nutritional habits